Formulation of deprivation index for identification of regional pattern of deprivation in rural India. (April 2021) - Basu, Tirthankar; Das, Arijit
Abstract: Deprivation of socio-economic well-being is one of the major reasons behind the occurrence of regional disparity in India. The present study has attempted to present and compare the regional pattern of deprivation in rural India by formulating a simple summary index of multidimensional deprivation (IMD) at the district level using global principal component analysis (PCA) and a Geographically Weighted Principal Component Analysis (GWPCA). The results of the study show that the east-central heartland of India is the most deprived region. On the contrary, the north and south India are in a much better position compared to the other part of the country. The results of the spatial autocorrelation of multidimensional deprivation (Global Moran's I = 0.748) indicates that there is a statistically significant pattern of spatial clustering that includes four distinct categories (High-High, Low-Low, High-Low, and Low-High). The LISA map shows that 151 districts belong to High-High (deprivation hotspots) and 108 districts come under the Low-Low cluster (deprivation cold spots). High-High cluster group spreads along with the ecologically sensitive areas like the Bastar region, Tarai tract, Chotonagpur region, and Dandakaranya region which are dominated by tribal populations. Highlights: Socio-economic deprivation is a prominent issue in India. 31 indicators are selected to analyze the character of deprivation. IMD is constructed based on PCA and GWPCA. 26 districts have an IMD value greater than 0.8. Rural areas of southern Chhattisgarh and Orissa are found as most deprived.